In-Kind Model in Creative Productive Zakat Funds: Case Study on National Zakat Administrator Agency (Baznas) of West Kalimantan Province - Sukma Indra; Muhammad Lutfi Hakim; Rofiul Wahyudi (Justicia Islamica, 2020)
The research results in this paper aim to describe the Small Business Capital Program's implementation, the constraints in implementing it, and the creative, productive zakat model that the Baznas of West Kalimantan Province have implemented in empowering the economy of Mustahiq. Therefore, the type of research used in this paper is field research with an empirical approach. Data collected from the results of interviews and documentation are then analyzed with qualitative data analysis. There are three research results in this paper. First, the Baznas of West Kalimantan Province implements the Small Business Capital Program to distribute zakat funds collected productively in venture capital. The venture capital is then bought the means of production and given to Mustahiq to start or develop a business that he already has. The aim is to change the status of mustahiq to muzakki the following year. Second, there are two obstacles experienced by Baznas of West Kalimantan Province in empowering the poor's economy through the Small Business Capital Program, namely the lack of human resources and the lack of zakat funds that the Baznas of West Kalimantan Province have collected. Third, the Small Business Capital Program at Baznas of West Kalimantan Province is included in the in-kind model to distribute creative, productive zakat funds. It is hoped that this in-kind model can be used as a solution and contribution to the government in reducing poverty, especially in West Kalimantan Province.